2014
DOI: 10.1002/14651858.cd010761.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating acute bleeding episodes in people with acquired hemophilia A

Abstract: No randomised clinical trials of hemostatic therapies for acquired hemophilia A were found. Thus, we are not able to draw any conclusions or make any recommendations on the optimal hemostatic therapies for acquired hemophilia A based on the highest quality of evidence. GIven that carrying out randomized controlled trials in this field is a complex task, the authors suggest that, while planning randomised controlled trials in which patients can be enrolled, clinicians treating the disease continue to base their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
2
0
3
Order By: Relevance
“…Moreover, out of 110 patients who received rFVIIa, one thromboembolic event was reported (16). However, two recent Cochrane reviews regarding the management of AHA reported that owing to the limited evidence, clinicians should base treatment on the available literature, usually in the form of case reports, case series, and observational studies (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, out of 110 patients who received rFVIIa, one thromboembolic event was reported (16). However, two recent Cochrane reviews regarding the management of AHA reported that owing to the limited evidence, clinicians should base treatment on the available literature, usually in the form of case reports, case series, and observational studies (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Moroccan epidemiological data on acquired hemophilia are not currently available, but its overall annual incidence is about 1–4 per million inhabitants, with an average age of 75 years and without any sex predominance [ 2 ]. Its pathogenesis is poorly understood and its prognosis remains severe [ 3 , 4 ]. Indeed, AH always surprises, and kills in 5–15% of cases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…НГА, як і спадкова гемофілія, призводить до спонтанних крововиливів, однак частіше в шкіру, м'язи, м'які тканини та слизову оболонку [1]. На відміну від спадкової гемофілії А, крововиливи в суглоби практично не виявляють або відмічають досить рідко [2,4,6]. Також, на відміну від спадкової гемофілії, клінічно вираженість і тяжкість перебігу хвороби не корелює з рівнем фактора згортання крові VIII (або іншого фактора, якщо це не гемофілія А) чи титром інгібітора [2,6].…”
unclassified
“…На відміну від спадкової гемофілії А, крововиливи в суглоби практично не виявляють або відмічають досить рідко [2,4,6]. Також, на відміну від спадкової гемофілії, клінічно вираженість і тяжкість перебігу хвороби не корелює з рівнем фактора згортання крові VIII (або іншого фактора, якщо це не гемофілія А) чи титром інгібітора [2,6]. Кровоточивість при НГА найчастіше тяжка, спонтанна та не пов'язана з жодним з відомих медичних станів.…”
unclassified
See 1 more Smart Citation